Numerical and experimental investigation of longitudinal rail creep at turnouts on steep ramps under repeated loads considering realistic braking loads of vehicles - Ma, Qiantao; Wang, Kai; Wang, Xian; Zheng, Zhaoguang; Li, Zhiheng; Fang, Jiasheng; Xiang, Kailai; Xu, Jingmang; Chen, Rong; Wang, Ping (Engineering failure analysis, 2023)
[Display omitted] •Under repeated loading, the boundary displacement between the elastic stage and the elastoplastic stage of longitudinal resistance of fasteners gradually increases, the maximum resistance decreases at the plastic stage.•Under repeated loading, the accumulated longitudinal residual displacement of turnout rails on ramp lines increases rapidly in the early stage, and then the growth gradually slows down and eventually stabilizes.•This paper proposes a method for analyzing the longitudinal rail creep at turnouts on steep ramps that can take into account the repeated action of realistic vehicle braking loads and the degradation effect of fastener resistance.•Full-scale experiment of the longitudinal rail creep at turnouts on steep ramps under repeated loading was carried out. Turnouts on steep ramps are subject to both temperature loads and frequent vehicle braking loads, which may lead to an accumulation of excessive residual longitudinal rail displacement, thereby leading to turnout service failure and threatening vehicle operation safety. In this paper, the following research work was carried out to study the longitudinal rail creep at turnouts on steep ramps: Experiments were conducted to investigate the longitudinal resistance characteristics of fasteners under repeated loading, and based on the experiment results, an MBS-FE simulation model was established for the longitudinal rail creep at turnouts on steep ramps, with real vehicle braking loads and fastener resistance degradation taken into consideration in the model. The change law for longitudinal displacement of turnout rails caused by temperature load and frequent vehicle braking load was studied based on the model. A full-scale experiment was then conducted on the longitudinal rail creep at turnouts on steep ramps under repeated loading conditions in order to verify the results of the simulation. A comprehensive and in-depth study of the longitudinal rail creep at turnouts on steep ramps impacted by repeated loading was conducted through the combination of theoretical analysis and experiment. The following conclusions were drawn: The longitudinal resistance of fasteners displays typical nonlinear characteristics and degrades under repeated loading, these characteristics lead to an obvious accumulation of residual longitudinal displacement of turnout rails on steep ramps under repeated loading, and the increment of residual longitudinal displacement of turnout rails reaches a maximum after the first loading–unloading cycle, and with the increase of the number of load action, the accumulated longitudinal residual displacement of turnout rails increases rapidly in the early stage, and then the growth gradually slows down and eventually stabilizes. The simulation results were found to be very similar to the full-scale experiment results, verifying the accuracy of the analytical model established in this paper.